1993
DOI: 10.1002/jsfa.2740620406
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, fatty acids and phenolic acids compositions of potato peels

Abstract: Abstract:The effects of freeze-dried extracts from the peels of six potato varieties as antioxidants in pure soy oil were investigated using the active oxygen method (AOM) procedure, carotene bleaching and linoleic acid oxidation experiments on thin-layer chromatography (TLC) plates. Results of the carotene bleaching and linoleic acid oxidation experiments on TLC plates indicated that the antioxidant activities of these extracts were due to the presence of phenolic acids. Among the phenolic acids separated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 14 publications
7
39
2
3
Order By: Relevance
“…Vitelotte analyzed by Hejtmánková et al (2009) showed high TPC in this respect and was similar to the Purple potato of Velioglu et al (1998) along with three of the Chilean potato genotypes shown in Table 2. Moreover, Onyeneho and Hettiaachchy (1993) evaluated the ability to prevent soybean oil oxidation of freeze-dried extracts taken from the peels of six potato varieties. They found that the peels from red potatoes contained greater amounts of polyphenols than those from brown-skinned varieties.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Vitelotte analyzed by Hejtmánková et al (2009) showed high TPC in this respect and was similar to the Purple potato of Velioglu et al (1998) along with three of the Chilean potato genotypes shown in Table 2. Moreover, Onyeneho and Hettiaachchy (1993) evaluated the ability to prevent soybean oil oxidation of freeze-dried extracts taken from the peels of six potato varieties. They found that the peels from red potatoes contained greater amounts of polyphenols than those from brown-skinned varieties.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Data on fatty acid composition in the seed oil of pomegranate also help to establish the chemotaxonomic relationships among the studied varieties, which have also been shown in some other species (Sundar Rao and Sin0 1992;Onyeneho and Hettiarachchy 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Yapılan in-vitro çalışmalarda kabuğun vitamin C, E ve fenolik bileşik içerdiği dolayısıyla da alternatif doğal antioksidan ve antimikrobiyal kaynağı olarak değerlendirilebileceği bildirilmiştir (Onyencho and Hettiarachchy, 1993;Nandita and Rajini, 2004;Al-Weshahy and Rao, 2009;Sarhan ve ark, 2010). Patates kabuğunun fenolik bileşik içeriğinin ve antioksidan aktivitesinin ortaya konduğu bir çalışmada (Rodriguez de Sotillo ve ark., 1994) su ekstraksiyonu ile elde edilmiş ve dondurularak kurutulmuş patates kabuğu ekstraktının %50,3 klorojenik, %41,7 kafeik, %7,8 gallik ve %0,21 protokateşik asit gibi fenolik bileşikleri içerdiği; ekstraktın ayçiçeği yağı oksidasyonunu önlemede BHA (butillenmiş hidroksianisol) kadar etkili olduğu bildirilmiştir.…”
Section: Antioksidan Ve Antimikrobiyal Olarak Değerlendirilmesiunclassified